CARE Peri-Urban Lusaka Small Enterprise (CARE PULSE) Project Zambia - Amuah, Alexander K. (World Bank, Washington, DC, 2012)
In January 1992, at the invitation of the Zambian Government, CARE International commenced operations in Zambia and set up a local branch named CARE Zambia. The initial focus of its programs was emergency relief in response to the severe drought of the early 1990s and interventions to militate against the effects of escalating inflation and extreme poverty in urban areas. Two years after its inauguration, CARE Zambia launched the Peri-Urban Lusaka Small Enterprise (PULSE) Project. The overall goal is to increase household income, economic security and employment opportunities among the families of poor micro-entrepreneurs in peri-urban areas of Zambia, through the provision of sustainable savings and credit services. The program provides working capital to micro and small-scale entrepreneurs, mostly women, who reside in the peri-urban areas of Mtendere and George. This service has recently been extended to Mandevu, Chawama and some peri-urban areas of Lusaka.